The labour insertion of asylum seekers in the Region of Murcia - Dricot, Marine; Boussif, Imad (Sociología del Trabajo, 2020)
The Spanish Law regulating the ’Right of Asylum and Subsidiary Protection’ ensures access to employment and vocational education and training programs for all applicants and beneficiaries of international protection (SBPI in Spanish) under the same conditions as national citizens. This study offers a quantitative documentary analysis, as well as a field work through in-depth interviews with the main protagonists: SBPI from Syria, Venezuela and Cameroon. As a result, the employment situation of this group in the Region of Murcia is characterised. The study concludes suggesting some improvements in the legal framework for labour market integration, highlighting the fact that the integration of asylum applicants and refugees in the labour market represents a good step stone to an increasingly inclusive welcome community.